Long-term trends in a northern Gulf of Mexico common bottlenose dolphin (Tursiops truncatus) population in the wake of the Deepwater Horizon oil spill - Balmer, Brian; Mcdonald, T.; Hornsby, F.; Allen, J.; Barleycorn, A.; Clarke, P.; Cush, C.; Honaker, A.; Mchugh, K.; Speakman, T.; Wells, R.; Schwacke, L. (J. Cetacean Res. Manage., 2018)
Bottlenose dolphins along the northern Gulf of Mexico continue to be impacted by numerous stressors including harmful algal blooms, infectious disease epizootics, and oil exposure following the Deepwater Horizon (DWH) oil spill. Studies to assess the potential impacts of the DWH oil spill on dolphins in the northern Gulf of Mexico were initiated as part of a Natural Resource Damage Assessment and included photographic-identification (photo ID) surveys to determine abundance, density, and site fidelity in St. Joseph Bay, Florida (SJB). Although significant oiling did not occur in SJB, long-term data have been collected in this region to provide insight into population-level trends in abundance/density over time. Thus, SJB dolphins could serve as a reference for comparison to other dolphin populations exposed to DWH oiling. During 2005–2007, the results of photo ID and telemetry surveys determined seasonal fluctuations in abundance and identified two different dolphin populations in SJB: residents sighted across multiple seasons and years (St. Joseph Bay Stock), and visitors that were present during the spring and fall and associated with a 2–3fold increase in abundance (Northern Coastal Stock). The goals for the current study were to compare dolphin abundance, density, and site fidelity, prior to (2005–2007), during (2010), and post-DWH (2011 and 2013) using photo-ID surveys and a spatially explicit robust-design capture-recapture (SERDCR) model. The data collected during and post-DWH paralleled previous research in that a low number of individuals with high site fidelity were sighted across seasons and years (St. Joseph Bay Stock), and abundance/density increased in the fall as a result of an influx of dolphins that were likely members of the Northern Coastal Stock. However, June and August 2010 abundance (347; 193–498, 95% CI and 394; 288–534, 95% CI, respectively), density (dolphins/km2) (2.60; 1.36–3.70, 95% CI and 2.55; 1.89–3.29, 95% CI, respectively), and site fidelity patterns were more similar to previous years’ spring and fall data, with high abundance estimates, increased dolphin density in coastal waters, and elevated numbers of individuals with low site fidelity in the SJB region. Factors that could have contributed to this increase in abundance include immigration of dolphins from adjacent estuaries, population growth within the St. Joseph Bay Stock, impacts from DWH oiling, and environmental and/or prey-based cues that influence movements of the Northern Coastal Stock. The results of this study demonstrate the importance of long-term monitoring to assess impacts of current and future stressors on the dolphins in the northern Gulf of Mexico.